Refeeding syndrome in critically ill children - Inas R. El-Alameey (Journal of the Arab Society for Medical Research, 2025)
Background Refeeding syndrome (RFS) is a metabolic disturbance that occurs when nutrition is reintroduced to individuals who are severely malnourished or experiencing significant metabolic stress from a serious illness. It results from underfeeding for a period, followed by re-initiation of nutritional support. The syndrome is characterized by sudden shifts in electrolytes, including phosphorus, magnesium, and potassium, and can be potentially fatal. Aim This review aimed to study children with RFS to understand the incidence, risk factors, and clinical outcomes associated with this condition. Specifically, research often focuses on determining how common RFS is among malnourished or critically ill children; identifying which children are most at risk, such as those with severe malnutrition or specific medical conditions; understanding the symptoms and complications that arise from RFS, including electrolyte imbalances and metabolic disturbances; and managing and preventing children with RFS through developing guidelines for safely reintroducing nutrition to malnourished children to prevent RFS. Conclusion Refeeding should start with a small increase in energy intake, along with supplementation of vitamins and electrolytes. Identification of patients who are at risk and early diagnosis before treatment and initiation of feeding is a crucial step in reducing RFS. Nutrition teams can offer guidance and education on preventing, recognizing, and treating RFS. Establishing local treatment guidelines is essential to support this process.